Higher education and ableism: Experiences of disabled students in England during the Covid-19 pandemic – stepping into inclusion - Suanne Gibson; Zeta Williams-Brown; Jen Shute; Mette Westander (Educational Futures)
This paper details the persistent and continuous struggles disabled students experience studying in HE, and how these were exaggerated during the Covid-19 pandemic (DSUK, 2020). We critically consider progress made by Widening Participation and related equality policy, determining that higher education (HE) continues to be an ableist system and space because inclusion is not understood, nor prioritised, at either strategic or practitioner levels. Furthermore, orthodox pathological positions on disability continue and are re-created via hegemony, ignorance, and fear (Madriaga, 2007; Gibson, 2020). Attempts at practices for the inclusion and equality of disabled students take place within the constraints of other policy objectives such as recruitment, standards, internationalisation, graduate outcomes and financial capacities (Gibson et al., 2016; Williams-Brown et al., 2022). The paper details key findings from a study by the authors, comparing them with national studies to consider consistent themes and implications for the future of an inclusive HE sector. The work determines what actions need to be taken in order to move forward effectively and inclusively for the progression and success of all students (DSC, 2020; DSUK, 2020; HEPI, 2020). We evidence that disabled students continue to have negative experiences of accessing, learning and progressing at university, which has longer term implications in terms of graduate outcomes. The paper concludes with recommendations including moving inclusion policy objectives on from their traditional ideological framing to focus on user-informed, user-led tried, tested and experienced inclusive education. It is argued that this move is taken in collaboration with senior leaders. We advocate for the position and expert knowledge of disability, as understood by disabled students to lead and evaluate change for inclusion, to inform what and how the HE sector evolves. Universities must be accountable for promoting inclusive changes in practice, geography and culture.